Do For-Profit Managers Spend Less on Schools and Instruction? A National Analysis of Charter School Staffing Expenditures. Issue 6 (September 2018) - Weber, Mark; Baker, Bruce
This article takes advantage of a recently released national data set on school site expenditures to evaluate spending variations between traditional district operated schools and charter schools operated by for-profit versus nonprofit management firms. Prior research has revealed the revenue-enhancement, private fund-raising capacity of major nonprofit providers. For-profit providers may face greater pressure to reduce operating expenses. As such, we hypothesize that regardless of average differences in staffing expenses between district and charter schools, school site staffing expenditures are likely to be lower in for-profit than in nonprofit managed charter schools. Furthermore, school site instructional staffing expenditures may be lower yet. Applying national, then state-level models to compare spending for schools of similar size, serving similar grade ranges and students with similar attributes (income status, special education, and language proficiency status), we find these assumptions largely to be true. Specifically, on average across all settings (global model) we find that charters spend less per pupil on instructional salaries compared with districts; furthermore, for-profit charters spend less than nonprofits. Furthermore, for-profit charters spend statistically significantly less ( p < .05) on instructional salaries, compared with district schools in many states.